MARKET VALUATION IN THE DIGITAL BANKING ERA: THE ROLE OF FINTECH ADOPTION AND FINANCIAL FRAUD - Sefira Nur Azizah; Gideon Setyo Budi Witjaksono (Universitas Tulungagung, 2026)
This study aims to analyze the influence of FinTech adoption and financial fraud on the market valuation of banking companies listed on the Indonesia Stock Exchange during the 2021–2024 period. Market valuation is measured using Price to Book Value (PBV), while FinTech adoption is proxied by the ratio of information technology expenses to total operating expenses, and fraud risk is measured using the F-Score model. This research applied a quantitative method using secondary data obtained from annual reports and financial statements of banking companies. The sample was determined through purposive sampling, resulting in 34 banking companies with 136 observation data. Data were analyzed using panel data regression with EViews 12 software. The findings reveal that FinTech adoption does not significantly affect market valuation, indicating that the implementation of financial technology has not fully enhanced the market value of banking companies. In contrast, financial fraud negatively affects market valuation, suggesting that higher fraud risk may reduce corporate credibility and investor trust. These results highlight the importance of effective financial fraud in maintaining banking company value amid the rapid digital transformation of Indonesia’s financial sector.